Sifat Fisikokimia dan Sensoris Tortilla dengan Penambahan Tepung Kacang Merah - Merynda Indriyani Syafutri; Friska Syaiful; Eka Lidiasari; Jery Mega Saputra (Seminar Nasional Lahan Suboptimal, 2021)
Syafutri MI, Syaiful F, Lidiasari E, Saputra JM.  2021. Physicochemical and sensory properties of tortilla  with red bean flour addition. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 771-781. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Red bean is one of Indonesia's local beans which contain high fiber and protein. Red bean also contain bioactive compounds (polyphenolic) that have antibacterial activity. Red bean processing is still not optimal, therefore the research is needed to examine the potential of red bean flour in making of tortillas. This research aimed to study the effect of red bean flour addition on physicochemical and sensory properties of tortilla. This study used a Completely Randomized Design. The factor was proportion of corn flour and red bean flour with eight level treatments (F) consisting of F1 (100% : 0%), F2 (90% : 10%), F3 (80% : 20%), F4 (70% : 30%), F5 (60% : 40%), F6 (50% : 50%), F7 (40% : 60%), and F8 (30% : 70%). The parameters were physical (color and texture), chemical (moisture, protein, and food fiber content), and sensory properties (taste, texture, and color). The results showed that the proportion of corn flour and red bean flour had significant effects on lightness, redness, yellowness, moisture content, and sensory properties (taste, texture, and color). Based on sensory properties and protein content, tortilla of F5 (60% corn flour : 40% red bean flour) was the best treatment.